Dimethyl Fumarate Reduces Microglia Functional Response to Tissue Damage and Favors Brain Iron Homeostasis. (15th July 2020) - Pagani, Francesca; Testi, Claudia; Grimaldi, Alfonso; Corsi, Giorgio; Cortese, Barbara; Basilico, Bernadette; Baiocco, Paola; De Panfilis, Simone; Ragozzino, Davide; Di Angelantonio, Silvia
Highlights: Dimethyl fumarate (DMF) is used to treat multiple sclerosis (MS), but very little is known on its mechanism of action. DMF treatment downregulates microglia functional response to ATP, affecting their ability to respond to tissue damages. Microglia treated with DMF show higher ferritin uptake, with possible impact in remyelination processes. DMF reduces microglia reactivity, pushing primary microglia towards an anti-inflammatory phenotype. Our results on microglia provide possible explanations to DMF drug effects on tissue repair in MS. Abstract: Dimethyl fumarate (DMF) is the only available approved drug for first line treatment of multiple sclerosis (MS), a lethal condition impairing central nervous system (CNS). To date, however, little is known of its mechanisms of action. Only recently, it has been suggested that DMF exerts neuroprotective effects acting as an immunomodulator and that it may alter the activation state of microglia cells, crucial in MS pathogenesis. However, DMF effects on microglia functions are still not well determined. Here, we examine the effects of DMF treatment on microglia functional activities, as phenotype, morphology, processes motility and rearrangement, migration, ATP response and iron uptake in mouse primary microglia culture and acute hippocampal slices. We found that DMF treatment reduces microglia motility, downregulating functional response to ATP, increases ferritin uptake and pushes microglia towards an anti-inflammatory phenotype, thus reducing its proinflammatory reactivity in response to tissue damage. These results highlight the effects of this compound on microglia functions and provide new insights on the mechanism of action of DMF in MS treatment.